Phenotypic diversity analysis and performance of elite lines of Brassica napus L. - Iqbal, Muhammad Sajjad; Akbar, Muhammad (Bangladesh Journal of Botany, 2021)
Thirteen elite lines of Brassica napus L. were tested. Nine phenotypic traits viz., days to 50% flowering, days to maturity, plant height, branches, pods, pod length, pod width, pod weight and seed yield were studied. ANOVA revealed significant results for all the traits while summary statistics exhibited high level of genetic variability in days to 50% flowering, days to maturity, plant height and number of pods. On the other hand, number of branches, pod length, pod width, pod weight and seed yield need more attention for improvement. Coefficient of correlation revealed significant combinations among various traits which could be utilized directly. Cluster analysis based on linkage distances described grouping pattern into three clusters for dissimilarities. Elite line 24866 of Pakistani origin placed in separate cluster prominently that is due to best performance for maximum traits, hence recommended for farmers’ field large scale cultivation.